QUESTIONS OF INTELLECTUALIZATION OF SCHOOLCHILDREN PHYSICAL EDUCATION PROCESS (Education in the 21st Century, 2023)
The leading factor in the social and biological human development is the formation of intellectual abilities. That is why, progressive intellectualization of activity is noted in different sciences, and this is also characteristic of physical education.In recent years, the terms “intellectualization of physical education” and “motor intelligence” are often used in specialized literature.Today “intellectualization” is considered as a process of forming the foundations of general physical culture knowledge, cognitive activity and the development of telekinetic intelligence among schoolchildren. Practice shows that the lack of theoretical knowledge of physical culture among students sharply reduces not only the effectiveness of training and education, but the interest in systematic physical exercises as well. Therefore, today new forms and ways of intellectual development in teaching are intensively searched. After the independence in Armenia six programs were introduced into the educational process on physical education.Unfortunately, in each year only six hours are allotted for theoretical training of schoolchildren which is too little.The article notes the urgent problems of the unity of intellectual and motor training of students in the process of physical education in comprehensive school. The author discusses and summarizes pedagogical issues in this direction.Having analyzed literature data, the experience of leading experts and the results of his own research, the author recommends a member of measures to implement the provisions of the intellectual vector of physical education in school, such as the obligatory presence of theoretical and practical sections, independent work and pedagogical testing and discussions, the use of intellectual motor tasks, ensuring the interconnection of motor and intellectual development of schoolchildren and so on.As a result of the work done, it was concluded that the process of teaching the basics of physical education and sports theory at school is still far from perfect.In order to increase the efficiency of this process, the lesson of physical education should carry, first of all, the educational function and provide intellectual theoretical preparedness, which ultimately will lead students to the formation of ideas about the capabilities of their own body, the ability to motor its condition, independently perform physical exercises throughout their life.Armenian population and the state as a whole will benefit from this. The intellectual vector of physical education should be inapplicable component of innovative pedagogical technologies in the practice of school physical education.